The Development and Distribution Pattern of Railway Network for Urban Public Transport Using GIS from 1990 Until 2019 in The Klang Valley and Kuala Lumpur, Malaysia - Yahya, Mohd Sahrul Syukri; Mohd Safian, Edie Ezwan; Burhan, Burhaida (Journal of Social Transformation and Regional Development, 2020)
The development and distribution pattern of the railway network has significantly increased in urban public transport with the current situation to move fast towards the fourth industrial revolution (4IR). In Malaysia, the problem issues are related to traffic congestion and many user cars on the roadway in daily lives. One alternative mode of using a rail network is commuter, LRT, Monorail, MRT and ETS. Therefore, the Geographic Information System (GIS) technology is then used to map and produce the railway networks history and developments in urban public transportation (UPT). The goal of this research is to identify the heatmap trends of the Klang Valley railway stations which included Kuala Lumpur as urban public transport sectors. It was based on the OSM image layer from the year 1990 to 2019 and studied the growth of railway networks through a polyline pattern analysis. The results are Kuala Lumpur and Klang Valley more advanced and dominant places in the event of rail and variation patterns in the year 1995 until 2019. The final result is that heatmaps of railway stations in Klang Valley and Selangor help determine and visualize the user’s attractive railway as the main public transport in daily routine and urban areas expand.